Urgensi Pelestarian Bahasa Sunda di Sekolah Dasar - Amelia Putri Wulandari; Dinie Anggraeni Dewi; Rizky Saeful Hayat (International Forum of Researchers and Lecturers, 2024)
Regional languages have a role more than just as a means of communication; it also functions as a symbol of pride, a marker of identity, and a means of communication within the family and local community. Nevertheless, regional languages face the challenge of extinction due to the influence of globalization, population migration, and lack of appreciation, especially among the younger generation. The method used is literature study. The focus of this article is on maintaining Sundanese in the context of elementary school education, highlighting the role of students as the main agents in maintaining regional languages. The discussion involves three key steps, namely learning, community activities, and the use of regional languages on special occasions. It is hoped that maintaining regional languages in education can create a generation that has strong character and is able to maintain cultural heritage, making the preservation of regional languages an important task to preserve cultural and linguistic diversity.